Rate of Photosynthesis and Features of Adaptation to Salinity of Cotton Varieties in Saline Soil Conditions (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
This article presents information on the effect of salinity on the rate of photosynthesis of cotton varieties grown over large areas of Uzbekistan. It was found that the rate of photosynthesis of the studied cotton varieties depends on the level of salinity. It was noted that the Bukhara-8 cotton variety is more resistant to salinity than the S-6524 variety. According to the scientific results obtained, salinity sharply reduced the rate of photosynthesis of both varieties. Among the studied varieties, it was found that the rate of photosynthesis in the Bukhara-8 variety is higher than in the S-6524 variety.